Risk factors associated with low birth weight in a polyclinic of Santiago de Cuba - Naifi Hierrezuelo Rojas; Alfredo Hernández Magdariaga; Marileydis Ávila Vázquez; Lourdes Marbelys Velázquez Ferreira; Roberto Alejandro Sotera Torres (Centro Provincial de Información de Ciencias Médicas, 2022)
Introduction: The low birth weight is considered an indicator of perinatal morbidity and mortality.  Objective: To identify the risk factors associated with low birth weight in a health area of Ramón Lopez Peña Teaching Polyclinic, in Santiago de Cuba.  Methods:  An observational analytic case-control study was carried out, that included 20 newborns with low birth weight (cases), and another group integrated by 80 infants, who didn't present this condition (controls), belonging to the health area abovementioned, from January to December, 2021. The ratio of crossed products, the confidence interval, chi-square test and the attributable risk in exposed percentage were determined.  Results: The preterm birth, multiple pregnancy and low maternal weight presented a ratio of crossed products of 13.7; 7 and 3.2, respectively. In a same way, it was elevated in the diseases related to pregnancy, such as anemia, hypertension and vaginal and urinary infections.  Conclusions: The inadequate weight at the first prenatal visit, preterm childbirth, multiple pregnancy and the presence of diseases related to pregnancy were the risk factors associated with low birth weight.